Grant Research Support in Russia: What Can We Learn from the Russian Science Foundation’s First Grant Competition? - Yuri Simachev; Ludmila Zasimova; Timur Kurbanov (Foresight and STI Governance)
This paper studies the Russian Science Foundation’s first grant competition, which was held in 2014 to select exploratory or basic research projects, in order to shed light on the following two questions: (1) who wins the grants, and (2) what factors are attributed to winning? The subsample of winners (when compared with the whole sample of applicants) seem to have higher proportions of projects submitted to the life sciences section, projects affiliated with the Russian Academy of Sciences (RAS) and projects from Moscow or the Moscow region. Besides, the heads of the winning projects had better publication indicators. We find that the main factor attributed to winning in the grant competition is the evaluation score given by external experts, while controlling for other factors. Although experts’ score is the most influential factor, the probability of receiving grant is strongly associated with others as well. Thus, projects affiliated with the RAS and with the head of the project holding a doctor’s degree have some advantages, all other factors being equal. Furthermore, projects from the regions and, most importantly, with young project heads, are more likely to win.